Real country : music and language in working-class culture. - Fox, Aaron A. (Duke University Press, 2004)
In Lockhart, Texas, a rural working-class town just south of Austin, country music is a way of life. Conversation slips easily into song, and the songs are full of conversation. Anthropologist and musician Aaron A. Fox spent years in Lockhart making research notes, music, and friends. In Real Country, he provides an intimate, in-depth ethnography of the community and its music. Showing that country music is deeply embedded in the textures of working-class life, Fox argues that it is the cultural and intellectual property of working-class people and not only of the Nashville-based music industry or the stars whose lives figure so prominently in popular and scholarly writing about the genre.